Deglacierization of a Marginal Basin and Implications for Outburst Floods, Mendenhall Glacier, Alaska - Kienholz, Christian; Pierce, Jamie; Hood, Eran; Amundson, Jason M.; Wolken, Gabriel J.; Jacobs, Aaron; Hart, Skye; Wikstrom Jones, Katreen; Abdel-Fattah, Dina; Johnson, Crane; Conaway, Jeffrey S. (Frontiers in Earth Science, 2020)
Suicide Basin is a partly glacierized marginal basin of Mendenhall Glacier, Alaska, that has released glacier lake outburst floods (GLOFs) annually since 2011. The floods cause inundation and erosion in the Mendenhall Valley, impacting homes and other infrastructure. Here, we utilize in-situ and remote sensing data to assess the recent evolution and current state of Suicide Basin. We focus on the 2018 and 2019 melt seasons, during which we collected most of our data, partly using unmanned aerial vehicles (UAVs). To provide longer-term context, we analyze DEMs collected since 2006 and model glacier surface mass balance over the 2006-2019 period. During the 2018 and 2019 outburst flood events, Suicide Basin released 30 million m3 of water within approximately 4 to 5 days. Since lake drainage was partial in both years, these 30 million m3 represent only a fraction (60%) of the basin's total storage capacity. In contrast to previous years, subglacial drainage was preceded by supraglacial outflow over the ice dam, which lasted 1 day in 2018 and 6 days in 2019. Two large calving events occurred in 2018 and 2019, with submerged ice breaking off the main glacier during lake filling, thereby increasing the basin's storage capacity. In 2018, the floating ice in the basin was 36 m thick on average. In 2019, ice thickness was 29 m, suggesting rapid decay of the ice tongue despite increasing ice inflow from Mendenhall Glacier. The ice dam at the basin entrance thinned by more than 5 m per year from 2018 to 2019, which is approximately double the rate of the reference period 2006-2018. While ice dam thinning reduces water storage capacity in the basin, that capacity is increased by declining ice volume in the basin and longitudinal lake expansion, with the latter process challenging to predict. The potential for premature drainage onset, intermittent drainage decelerations, and early drainage termination further complicates prediction of future GLOF events.